Implementasi Digitalisasi dan Teknologi Untuk Perkembangan dan Strategi Bisnis Kru V Jasa Pengelola Sosial Media dari Sisi Pemasaran - Bobby Dewantoro; Moh. Farid Hidayat; Talita Karisma Syaharani; Anggita Dana Salsa Bila; Rheiza Marell Anugerah (International Forum of Researchers and Lecturers, 2024)
This journal discusses the implementation of digitization and technology as key drivers for advancing and designing business strategies for Kru V, a social media management service agency. In an era where social media plays a crucial role in marketing and customer interaction, the agency leverages digital technology to enhance operational efficiency and broaden the scope of its services. This article provides an in-depth analysis of the concrete steps taken by Kru V in adopting cutting-edge technology and its impact on the agency's business development and competitive advantage.